Ecoprint: Upaya Mengurangi Paparan Digital pada Anak Melalui Sekolah Perempuan Kreatif Batursari - Trisnapradika, Gustina Alfa; Amri, Sahrul; Ardiansyah, Nibras Bahy; Rozada, Akfi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Golden Age is an era for children which is most crucial in building character in the future. However, nowadays many children are exposed to gadgets from an early age. The role of parents is very important to facilitate creative and positive activities to divert children's addiction to gadgets. Ecoprint is one of the activities that can be done with children. So, the service team held a service in the form of ecoprint training which was attended by women from Desa Batursari who are members of the Batursari Creative Women's School. As a result, participants took part in the training enthusiastically and produced good creations. The hope is that this activity can be an idea for playing with children at home.